How Effective is Differentiated Instruction Model for Special Needs Students? Perspectives of Inclusive Teachers - Muksalmina, Muksalmina; Istiarsyah, Istiarsyah; Kamarullah, Kamarullah; Sabaruddin, Sabaruddin (Angstrom Centre of Education, 2024)
In Indonesia, the inclusion of special needs children in mainstream education poses significant challenges, necessitating effective instructional strategies to meet their diverse learning needs. This study explores the effectiveness of Differentiated Instruction (DI) models in inclusive schooling settings, aiming to assess their impact on the learning outcomes and experiences of special needs children. Through telephone interviews with six teachers representing diverse educational backgrounds, this research delves into their experiences with implementing DI models. Thematic data analysis was employed to identify patterns, themes, and challenges associated with using DI in inclusive classrooms. The findings shed light on the effectiveness of various instructional strategies in meeting the unique needs of special needs children, while also uncovering barriers to effective implementation such as limited resources and inadequate training. Preliminary results indicate that DI models have the potential to enhance the learning experiences and outcomes of special needs children within inclusive settings. Teachers reported increased student engagement, motivation, and academic progress when employing tailored instructional approaches. However, challenges such as resource constraints and lack of training emerged as hindrances to effective DI implementation. This study underscores the importance of adopting student-centered instructional approaches to accommodate diverse learning needs in inclusive classrooms. Furthermore, it highlights the necessity for targeted professional development programs and resource allocation to support teachers in effectively implementing DI strategies. By contributing insights into best practices for supporting the educational success of special needs children in mainstream schools, this research adds to the ongoing discourse on inclusive education in Aceh.